Polystyrene nanoparticles impair endometrial decidualization in early pregnant mice via oxidative stress-driven autophagy suppression and ferroptosis induction - Li-Qing Wang; Qian-Feng Qiao; Huang-Nian You; Yi-bin Zheng; Xiao-Mei Wu; Wen-Jie Yu; Zeng Liu; Wen-Juan Song; Lin-Hong Zhang; Jia-Rui Hu; Xin-Yu Mao; Yong-Jiang Zhou (Food and Chemical Toxicology, 2026)

Level terraces enhance the vertical distribution of soil organic carbon in mixed forests: microbial mechanisms and carbon fraction dynamics on the loess plateau - Zhe Li; Ning Zhang; Zi-ming Wang; Rui-kun Feng; Yi-qiao Chen; Zheng-hua Liu; Wen-fan Wang; Jia-bin Liu; Jian Wang (CATENA, 2026)

Safety and efficacy of recombinant botulinum toxin type A (Eveotox®) in patients with post-stroke upper limb spasticity: Results from a Phase Ib/II clinical trial - Rongrong Lu; Lingjing Jin; Jianzhong Xiong; Lixin Zhang; Yaling Liu; Leilei Xu; Rui Wu; Jianhua Tang; Liandong Zhao; Lihua Dong; Weifeng Luo; Yu Pan; et al. (Toxicon, 2026)

Lateral impact performance of concrete-encased concrete-filled steel tubular (CECFST) members after exposure to fire: Tests and analysis - Yuan Zheng; Wen-Da Wang; Sun-Hang Ji; Yan-Li Shi; Wei Xian; Rui Wang (Engineering Structures, 2026)

Waste akebiae trifoliata-derived WO3 hierarchical tubes efficient detection of ppb-level triethylamine gas at low temperature and application in food freshness detection - Wen-Xiao Li; Jia-Wang Wang; Rui-Long Li; Qiu-Yue Zheng; Bao-Yu Song; Bo-Ya Liu; Li-Xia Zhao; Ying Fu; Ying-Ming Xu (Chemical Engineering Journal, 2026)

Low-cost pillar-ligand engineering toward ultramicroporous MOFs for efficient SF6/N2 separation - Biao Fu; Hui-Ting Zheng; Rui-Ming Li; Duo Yue; Liang Song; Zhang-Wen Wei; Robert Langer; Mihail Barboiu; Ji-Jun Jiang; Cheng-Yong Su (Chemical Engineering Journal, 2026)

A lyophilized RPA–CRISPR/Cas13d one-pot platform for rapid detection of porcine circovirus type 3 - Li-Na Shao; Zheng-Luo; Bao-Ling Liu; Tong-Xu; Yuan-Meng Wang; Jia-Qi Duan; Lei-Zhao; You-You Li; Yang-Ming Dai; Qin-Rui Jia; Le-Yi Zhang; Ling-Zhu; et al. (Analytica Chimica Acta, 2026)

CXCL8 is associated with aflatoxin B1–triggered injury and caspase-3 activation in porcine kidney epithelial PK15 cells: integrated transcriptomics and CRISPR/Cas9 knockout - Jianlin Yuan; Yuhan Ma; Jinfeng Li; Xizhu Chen; Yiping Wen; Rui Wu; Xinfeng Hang; Heng Huang; Senyan Du; Yiping Wang; Qi-Gui Yan; Xiaobo Huang; et al. (Food and Chemical Toxicology, 2026)

Metal covalent organic frameworks with donor-acceptor-catalytic site (D-A-C) for boosting CO2 photoreduction - Shi-Wen Zhang; Wen-Yi Zheng; Shu-Zhi Hu; Qian-Rui Mao; Mi Tian; Wang-Kang Han; Zhi-Guo Gu (Chemical Engineering Journal, 2026)

Engineered MBene-integrated anisotropic aerogel with synergistic hydrogen-bond network and superior photothermal conversion for efficient solar-driven desalination and purification - Xinyi Wang; Rongtao Zheng; Cuilian Wen; Lijin Luo; Jiansen Wen; Haonan Zhao; Rui Xiong; Frank Marken; Yin Yuan; Baisheng Sa (Desalination, 2026)

Influence of Rate Effects on Fracture-Induced Opening of Interlayer Branch Fractures - Wen-rui Wang; Zong-qing Zhou; Hua-qing Ma; Xue-lin Zheng; Lei Chen; Cheng-lu Gao; Zhi-yuan Liu (Rock Mechanics and Rock Engineering, 2026)

The association of long-term exposure to PM1 with dyslipidemia in Chinese older adults and the modifying role of vitamin D - Pengjing Yao; Rui Zhang; Xuqiu Cheng; Xinyu Kou; Ziwei Tian; Jinmin Zheng; Yan Zhang; Xianwei Guo; Bing Hu; Changliu Liang; Yufeng Wen; Fangbiao Tao; et al. (Atmospheric Pollution Research, 2026)

The evaluation to combined toxic effects of polypropylene microplastics and benzo[a]pyrene on macrophage cells - Ye-xuan Zhang; Rui Hou; Si-si Chen; Xue-wen Guo; Hong-juan Chen; Li Mao; Wei-juan Zheng; Hong-zhen Lian (Science of The Total Environment, 2026)

Revisit the improvement of coagulation pretreatment on ozonation performance: The critical roles of HO• and O3 for effluent organic matter transformation and micropollutant degradation - Rui Hu; Hao-Tong Zheng; Boxi Tang; Jialing Tu; Yu-Hong Cui; Xuedong Zhai; Gang Wen; Zheng-Qian Liu (Journal of Cleaner Production, 2026)

Laminarin attenuates neuroinflammation in MPTP-induced Parkinson’s disease mouse model via inhibiting dectin-1/Syk/NF-κB signaling - Rui-Yue Zhao; Mei Zhang; Xiao-Wen Wang; Feng Xue; Yang-Yang Zheng; Wen-Fang Chen (Inflammopharmacology, 2026)

Raccoon dog parvovirus NS1 protein antagonizes type I interferon signaling by promoting selective autophagic degradation of IRF3 - Wen-yu Cao; Rui-qi Wang; Jin-yang Zheng; Ping Ma; Bo Hu; Cheng-qi Zhang; Ya-jie Sun; Jia-jia Liu; Ding-rui Guo; Zi-han Zhao; Xin Cao; Xue Bai; et al. (Veterinary Microbiology, 2026)

Clostridium dalinum: A Novel Lactic Acid Bacterium with Excellent Antioxidant and Anti-inflammatory Functions Through NF-κB, Keap1-Nrf2-ARE Signaling Pathways - Zheng-Qiang Li; Rui Li; Wei Deng; Rui An; Ping Ma; Jun Li; Rong She; Xiao-Yan Yang; Xu Yang; Wen Xiao (Probiotics and Antimicrobial Proteins, 2026)

Isothiazolinone biocide aggravate disinfection-resistant bacterial fouling on reverse osmosis membranes - Yu-Qing Xu; Zheng-Yang Huo; Yuan Bai; Yun Wang; Wen-Long Wang; Hao-Bin Wang; Yu-Jia Gao; Rui-Ning Wang; Chen-Yu Li; Han Liu; Wei E. Huang; Hong-Ying Hu; et al. (Desalination, 2026)

Changes in soil multifunctionality under different grazing intensities in spring are mainly influenced by the stability of soil biota networks - Hansen Gao; Rui Wang; Yali Yin; Wen Zhao; Wenxian Zheng; Xueao Song; Haiqiang Liu; Shixiong Li (Agriculture, Ecosystems & Environment, 2026)

Rare earth element hyperaccumulation in vascular plants: Occurrence, mechanisms, and applications - Ruo-Rong Liu; Cui-Ling Huang; Hong-Xiang Zheng; Chong Liu; Rui-Qi Zhang; Yue Cao; Antony van der Ent; Can-Die Xie; Wen-Shen Liu; Jean Louis Morel; Catherine Sirguey; Damien Blaudez; et al. (Critical Reviews in Environmental Science and Technology, 2025)

Contrasting geochemistry of apatite from the Jurassic W- and Sn-mineralized granites in the Qitianling field, Nanling Range, South China - Hongfei Di; Yong-Jun Shao; David Chew; Rui-Chang Tan; Han Zheng; Yong Liang; Wen-Jie Fang; Yi-Qu Xiong (Lithos, 2025)

Enhancing performance of SSVEP-based visual acuity via exploiting subject-specific information - Xiaowei Zheng; Boyu Wen; Xin Yan; Guanghua Xu; Rui Zhang (Cognitive Neurodynamics, 2025)

A new genus and species of Susumaniidae (Insecta: Phasmatodea) from the Middle Jurassic of Shaanxi Province, Northwest China - Qi-Ming Guo; Chun-Peng Xu; André Nel; An-Cheng Peng; Zhi-Gang Wen; Ting Li; Rui Fang; Da-Ran Zheng (Palaeoworld, 2025)

Metal salt modulation strategy to prepare highly defective coal-based porous carbon for solid-state zinc ion hybrid capacitors - Pengxu Ren; Haolan Wen; Tao Wang; Yafen Zheng; Rui Sheng; Dongling Wu (Chemical Engineering Journal, 2025)

A balanced approach to the potential of octopus aquaculture - Ian G. Gleadall; Roger Villanueva; Gregory J. Barord; Zoe Doubleday; Felipe Aguado-Giménez; Nobuhiko Akiyama; Eduardo Almansa; Cheryl L. Ames; Alexander Arkhipkin; Otilio Avendaño; Chris Barrett; Giambattista Bello; et al. (Marine Policy, 2025)

Recycling traditional Chinese medicine residues: a review - Xiaowei Wu; Dai Dai; Na Li; Haixin Zheng; Cuixia Wang; Weixiong Lin; Liaoyuan Liu; Zheng Zhang; Jörg Rinklebe; Carol Sze Ki Lin; Wen Rui; Chong Li (Environmental Chemistry Letters, 2025)
Traditional Chinese medicine has a rich history in the diagnosis and treatment of diseases, yet the disposal of medicine residues by incineration and landfilling is challenging. Here we review methods to recycle Chinese medicine residues with focus on challenges, recycling solutions, and case studies. Cases studies include extraction of bioactive compounds, use as feed additives, and biochar-based materials. We observed that residues from single-compound medicines are easier to extract and recycle into animal feed additives or adsorbents. Technical and economic analysis show that the valorisation of single-compound medicine residues is profitable. For instance, the re-extraction cost of flavonoids is 25.8–36.6% lower than the market price, and the cost as feed additives represents 14.7% of the market prices.

The long noncoding RNA VIVIpary promotes seed dormancy release and pre-harvest sprouting through chromatin remodeling in rice - Lu Yang; Yu Cheng; Chao Yuan; Yan-Fei Zhou; Qiao-Juan Huang; Wen-Long Zhao; Rui-Rui He; Jie Jiang; Yi-Chao Qin; Zheng-Tong Chen; Yu-Chan Zhang; Meng-Qi Lei; et al. (Molecular Plant, 2025)

Rubrolithibacter danxiaensis gen. nov., sp. nov. isolated from red sandy conglomerate in the Danxia Mountain - Wen-Hui Lian; Huan-Huan He; Ying Wang; Zhuo-Huan Zheng; Fang Chen; Ting Zhou; Chao-Jian Hu; Jia-Rui Han; Lei Dong; Wen-Jun Li (Antonie van Leeuwenhoek, 2025)

Urinary concentrations of phthalate metabolites and the survival of high-grade serous ovarian cancer with advanced stage - Wen-Rui Zheng; Yi-Zi Li; Jin Xu; Ke-Xin Liu; Fang-Hua Liu; Wei-Yi Xing; Jia-Xin Liu; Lang Wu; Xiao-Ying Li; Dong-Hui Huang; Ting-Ting Gong; Qi-Jun Wu (Environmental Pollution, 2025)

Insight of oil-soluble Fe-based catalyst for direct liquefaction of Shangwan coal - Zhi Li; Yuxin Wen; Rui Zhang; Mei Zhong; Haiyun Liu; Xin Zheng; Haoquan Hu; Lijun Jin (Fuel, 2025)

Enhanced regeneration of large segmental bone defects via hierarchically structured bioactive scaffolds - Mo-Han Wang; Shao-Meng Wen; Yun-Hong Cong; Huai-Ling Gao; Xian-Yu Zheng; Zi-Xiang Han; Run Wang; Rui Xu; Lu Yang; Wen-Jing Li; Zhao Pan; Jia-Cai He; et al. (Chemical Engineering Journal, 2025)

Isolation and detection strategies for decoding the heterogeneity of extracellular vesicles - Shi-Ming Wang; Dan Wang; Yu-Qing Shen; Mo-Han Wang; Fei Jia; Zhao Pan; Liang Dong; Xian-Yu Zheng; Hui-Qin Wen; Rui Xu (Chemical Engineering Journal, 2025)

Estradiol Enhances Cerebellar Molecular Layer Interneuron-Purkinje Cell Synaptic Transmission and Improves Motor Learning Through ER-β in Vivo in Mice - Yong-Rui Piao; Mei-Rui Li; Ming-Ze Sun; Yang Liu; Chao-Yue Chen; Chun-Ping Chu; Yuki Todo; Zheng Tang; Chun-Yan Wang; Wen-Zhe Jin; De-Lai Qiu (The Cerebellum, 2025)

Enrichment characteristics of Cd and Hg and regulation of heavy metal transporter signaling in Pleurotus ostreatus - Qing Liu; Xiukun Zheng; Rui Du; Yuqiang Shao; Qing Wen; Xiaoye Shen; Fengqin Wang; Yuancheng Qi; Jinwen Shen; Yanru Hu (Science of The Total Environment, 2024)

Highly stable zinc anodes enabled by a dual-function additive of in-situ film formation and electrostatic shielding - Rui-han Ji; Hao Fu; Qing Wen; Pei-Yao Li; Pei Yang; Yu-Jing Chen; He-zhang Chen; Jia-feng Zhang; Ling-jun Li; Jie-xi Wang; Qing Wu; Xia-hui Zhang; et al. (Chemical Engineering Journal, 2024)

Cyanide content, nutrient composition, physicochemical properties and sensory quality of flaxseed oil bodies prepared from flaxseeds (Linum usitatissimum L.) treated with different heat treatment methods - Rui Zheng; Hui-Lin Liu; Nan-Nan Cui; Jun-Zhuo Zhou; Xin Sun; Fa-Wen Yin; Da-Yong Zhou (Food Research International, 2024)

Molecular characterization, spatio-temporal expression patterns of crtc2 gene and its immune roles in yellow catfish (Pelteobagrus fulvidraco) - Wan-Hong Zeng; Zheng-Yong Wen; Xiu-Ying Wei; Yu He; Luo Zhou; Peng Hu; Qing-Chao Shi; Chuan-Jie Qin; Jun Wang; Rui Li; Xiao-Ying Jing; Wei Hu; et al. (Fish & Shellfish Immunology, 2024)

Six element high-entropy Prussian blue analogue cathode enabling high cycle stability for sodium-ion batteries - Zhe Qian; Rui-Jie Luo; Cui Ma; Chong-Yu Du; Jie Zeng; Xuan Xu; Zhe Mei; Zi-Ting Zhou; Zheng-Wen Fu; Yong-Ning Zhou (Chemical Engineering Journal, 2024)

Suppression the glucose-induced ferroptosis in endothelial cells by 4OI-loading exosomes hydrogel for the treatment of diabetic foot ulcer - Kuo Shen; Rui Zheng; Bangrui Yu; Hao Zhang; Peng Wang; Peng Zhao; Jijun Chen; Yixuan Yuan; Yuhang Wang; Kejia Wang; Yanhui Jia; Ruizhi Wang; et al. (Chemical Engineering Journal, 2024)

Metformin improves cognitive dysfunction through SIRT1/NLRP3 pathway–mediated neuroinflammation in db/db mice - Tian Hu; Jun-Wen Wei; Jia-Yi Zheng; Qing-Yi Luo; Xin-Rui Hu; Qun Du; Ye-Feng Cai; Shi-Jie Zhang (Journal of Molecular Medicine, 2024)

Adaptation mechanisms of soil microbial community to stoichiometric imbalances caused by forest conversion - Xianzhen Luo; Lingling Zhang; Zhi Li; Rui Zhang; Johannes J. Le Roux; Jason K. Reynolds; Hanxia Yu; Minghao Chen; Yahong Zheng; Enqing Hou; Dazhi Wen (Applied Soil Ecology, 2024)

Molecular characterization of fad6 gene and its transcriptional changes in response to different initial diets and nutritional status in yellow catfish (Pelteobagrus fulvidraco) - Bo Zhou; Xiu-Ying Wei; Zheng-Yong Wen; Bin Wang; Yu-Ying Zhao; Wan-Hong Zeng; Yu He; Panita Prathomya; Yun-Yun Lv; Yan-Ping Li; Jun Wang; Rui Li; et al. (Frontiers in Marine Science, 2024)
Fatty acid desaturases (FADs) are rate-limiting enzymes for the biosynthesis of highly unsaturated fatty acids (HUFAs). As a new member of the FAD family, Fad6 and its roles remain unclear in various teleost fishes. In this study, we identified a fad6 gene from yellow catfish (yc fad6 ) and determined its spatiotemporal expression patterns and responses to different initial diets and nutritional status in yellow catfish. Our results showed that the open reading frame (ORF) of yc fad6 was 1,080 bp in length, encoding a protein of 359 amino acids. Multiple protein sequences alignment proved that fad6 is highly conserved among diverse vertebrates. Meanwhile, phylogenetic analysis revealed that Southern catfish and yellow catfish were clustered into one branch, supporting evolutionary consistence between the fad6 gene and fish morphology. Moreover, comparisons of genomic synteny and gene structure revealed functional and evolutionary conservation of the fad6 gene in various teleost fishes. Tissue distribution analysis by quantitative RT-PCR demonstrated that the yc fad6 gene was extensively expressed in examined tissues, with higher transcription levels in the heart and liver. Meanwhile, yc fad6 gene was widely expressed in various developmental stages, indicating Fad6 may play important roles in HUFA biosynthesis at early developmental stages in yellow catfish. Functional experiments verified that the transcription of yc fad6 decreased significantly with the extension of feeding time (with egg yolk or Artemia nauplii ) at the early developmental stages, indicating that a diet rich in HUFA can remarkably inhibit the transcription of yc fad6 in yellow catfish. In addition, yc fad6 transcription was significantly reduced after a short-term (24-h) or long-term food deprivation (1-week) and then continued to decrease during refeeding, suggesting that nutritional states can affect the transcription of yc fad6 , which further regulates the metabolism of HUFAs. Anyway, these fundamental findings provide basic references for further investigating evolutionary and physiological functions of the fad6 gene in yellow catfish as well as in other teleost fishes.

Cement-based external wall insulation material with thermal performance improvement by partial substitution of calcium silicate - Wen Rui Ren; Cheng Hai Wang; Chang Bao Han; Dong Han; Jia Yu Zheng; Ya Nan Cui; Xue Mei Song; Quan Jiang; Hui Yan (Energy and Buildings, 2024)

Distribution, risk evaluation, and source allocation of cesium and strontium in surface soil in a mining city - Jia-li Li; Chun-dan Gan; Xin-yue Du; Xue-ying Yuan; Wen-lin Zhong; Meng-qi Yang; Rui Liu; Xiao-yu Li; Hao Wang; Yu-liang Liao; Zheng Wang; Mu-cheng Xu; et al. (Environmental Geochemistry and Health, 2024)

Per- and polyfluoroalkyl substances and human health outcomes: An umbrella review of systematic reviews with meta-analyses of observational studies - Wei-Yi Xing; Jia-Nan Sun; Fang-Hua Liu; Li-Shen Shan; Jia-Li Yin; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Jia-Xin Liu; Wen-Rui Zheng; Ying-Ying Zhang; Xin-Jian Song; et al. (Journal of Hazardous Materials, 2024)

A newly isolated strain of Bacillus subtilis W2Z exhibited probiotic effects on juvenile red claw crayfish, Cherax quadricarinatus - Ze-Long Zhang; Jia-Jun Li; Si-Wen Xing; Yao-Peng Lu; Pei-Hua Zheng; Jun-Tao Li; Chen-Guang Hao; Jia-Rui Xu; Jian-An Xian; Li-Min Zhang; Xiu-Xia Zhang (Aquaculture, 2024)

Slope Stability Analysis under Heavy Rainfall Conditions Based on a Modified Green-Ampt Model - Yunxin Zheng; Zhiping Hu; Rui Wang; Xin Wen; Xiang Ren; Rui Pan (Water Resources Management, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

Structural elucidation of a non-starch polysaccharides from Lilii Bulbus and its protective effects against corticosterone-induced neurotoxicity in PC12 cells - Yili Zheng; Xueying Li; Danna Lin; Jian Wu; Yufei Tian; Hongyuan Chen; Wen Rui (Glycoconjugate Journal, 2024)

Aridity drives the variability of desert soil microbiomes across north-western China - Lei Dong; Mei-Xiang Li; Shuai Li; Ling-Xiang Yue; Mukhtiar Ali; Jia-Rui Han; Wen-Hui Lian; Chao-Jian Hu; Zhi-Liang Lin; Guo-Yuan Shi; Pan-Deng Wang; Shao-Ming Gao; et al. (Science of The Total Environment, 2024)

Lipopolysaccharides from a Shiraia fruiting body-associated bacterium elicit host fungal hypocrellin A biosynthesis through nitric oxide generation - Xin Ping Li; Wen Hao Shen; Lu Lu Zhou; Qun Yan Huang; Rui Peng Cong; Li Ping Zheng; Jian Wen Wang (Carbohydrate Polymers, 2024)

CD4 is an important host factor for Japanese encephalitis virus entry and replication in PK-15 cells - Qi Wang; Shuqing Yang; Ke Yang; Xinran Li; Yu Dai; Yi Zheng; Sanjie Cao; Qigui Yan; Xiaobo Huang; Yiping Wen; Qin Zhao; Senyan Du; et al. (Veterinary Microbiology, 2023)

Bamboo polysaccharides elicit hypocrellin A biosynthesis of a bambusicolous fungus Shiraia sp. S9 - Wen Hao Shen; Lu Lu Zhou; Xin Ping Li; Rui Peng Cong; Qun Yan Huang; Li Ping Zheng; Jian Wen Wang (World Journal of Microbiology and Biotechnology, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Adaptability of wheat to future climate change: Effects of sowing date and sowing rate on wheat yield in three wheat production regions in the North China Plain - Pengfei Wen; Qiongru Wei; Liang Zheng; Zhanxu Rui; Mengjiao Niu; Chenkai Gao; Xiaokang Guan; Tongchao Wang; Shuping Xiong (Science of The Total Environment, 2023)

Soil phosphorus availability mediates facilitation dynamic in maize-grass pea intercropping system - Shuang-Guo Zhu; Wesly Kiprotich; Zheng-Guo Cheng; Rui Zhou; Jing-Wei Fan; Hao Zhu; Wen-Ying Wang; Wei Wang; Ren-Qing Wang; Hong-Yan Tao; You-Cai Xiong (Soil and Tillage Research, 2023)

Two new bibenzyls from Pleione grandiflora (Rolfe) Rolfe and their antioxidant activity - Wei Li; Jia-Rui Fu; Li-Jun Zheng; Lin Ni; Jun-Qing Liu; Jun-Wen Zhai; Zhuang Zhou; Sha-Sha Wu (Natural Product Research, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Intraspecific variations of adaptive strategies of native and invasive plant species along an elevational gradient - Hasigerili; Kun Guo; Miao-Miao Zheng; Rui-Ling Liu; Yan-Yan Wang; Yuan Gao; Li Shu; Xiao-Ran Wang; Jian Zhang; Wen-Yong Guo (Flora, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

Exposure to real-ambient particulate matter induced vascular hypertrophy through activation of PDGFRβ - Hongxu Bao; Benying Li; Qing You; Xinyu Dun; Zhen Zhang; Yanan Liang; Yahui Li; Qixiao Jiang; Rong Zhang; Rui Chen; Wen Chen; Yuxin Zheng; et al. (Journal of Hazardous Materials, 2023)

Extreme cooling of 12.5 °C triggered by Typhoon Fungwong (2008) - Zhe-Wen Zheng; Jia-Yi Lin; Ganesh Gopalakrishnan; Yi-Rui Chen; Doon-Jing Doong; Chung-Ru Ho; Quanan Zheng; Chau-Ron Wu; Chen-Fen Huang (Ocean Modelling, 2023)

An in-situ strategy to construct uracil-conjugated covalent organic frameworks with tunable fluorescence/recognition characteristics for sensitive and selective Mercury(II) detection - Xi-Rui Deng; A-Wei Hu; Sheng-Qian Hu; Wen-Li Yang; Chen Sun; Sai-Jin Xiao; Gui-Ping Yang; Qiong-Qing Zheng; Ru-Ping Liang; Li Zhang; Jian-Ding Qiu (Analytica Chimica Acta, 2023)

Quality prediction of tractor rotary tillage based on BiConvLSTM with self-attention - Ruo-chen Li; Chang-kai Wen; Shu-yan Li; Rui Li; Hong-yu Pu; Yu Jiang; Zheng-he Song (Computers and Electronics in Agriculture, 2023)

Exposure to cadmium induced gut antibiotic resistance genes (ARGs) and microbiota alternations of Babylonia areolata - Wang Zhao; Qian Han; Rui Yang; Weigeng Wen; Zhenghua Deng; Huan Li; Zhongming Zheng; Zhenhua Ma; Gang Yu (Science of The Total Environment, 2023)

Machine learning approaches to predict the apparent rate constants for aqueous organic compounds by ferrate - Shan-Shan Zheng; Wan-Qian Guo; Hao Lu; Qi-Shi Si; Bang-Hai Liu; Hua-Zhe Wang; Qi Zhao; Wen-Rui Jia; Tai-Ping Yu (Journal of Environmental Management, 2023)

Molecular characterization of a teleost-specific toll-like receptor 22 (tlr22) gene from yellow catfish (Pelteobagrus fulvidraco) and its transcriptional change in response to poly I:C and Aeromonas hydrophila stimuli - Xiu-Ying Wei; Jun Wang; Sheng-Tao Guo; Yun-Yun Lv; Yan-Ping Li; Chuan-Jie Qin; Yuan-Chao Zou; Qing-Chao Shi; Peng Hu; Xiao-Qin Xiong; Yang He; Rui Li; et al. (Fish & Shellfish Immunology, 2023)

MiR-130/SNAP-25 axis regulate presynaptic alteration in anterior cingulate cortex involved in lead induced attention deficits - Tao Wang; Rui-Li Guan; Yun-Feng Zou; Gang Zheng; Xue-Feng Shen; Zi-Peng Cao; Rui-Hua Yang; Ming-Chao Liu; Ke-Jun Du; Xue-Hang Li; Michael Aschner; Ming-Gao Zhao; et al. (Journal of Hazardous Materials, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Influences of Tidal Effect on Upper Ocean Responses to Typhoon Passages Surrounding Shore Region off Northeast Taiwan - Zhe-Wen Zheng; Yi-Rui Chen (Journal of Marine Science and Engineering, 2022)
In this study, the Regional Ocean Modelling System (ROMS) with a spatial resolution of 2 km is used to understand the cooling responses in the sea northeast of Taiwan associated with multiple typhoons. Sea level measurements derived from in situ tidal gauges and continuous temperature measured by a moored buoy deployed at Longdong were used to validate the model’s performance. Six far-field typhoons with similar tracks, namely, Utor (2001), Dujuan (2003), Sanvu (2005), Nanmadol (2011), Usagi (2013), and Meranti (2016), were systematically investigated to demonstrate the influences of tidal effect on upper ocean responses to typhoon passages surrounding shore regions. After integrating tidal forcing, model-simulated cold wakes behind typhoon passages were essentially enhanced. Compared with observations, the cold wakes were reproduced more realistically. Tides could promote a cooling response through the following potential mechanisms: (1) tidal mixing destratifies the water column, (2) a stronger northward current leads to a sharper bottom thermocline, (3) tidal residual currents (southward) drive the offshore-ward (downslope) bottom Ekman flow and lead to the overturning of cold bottom water and warm subsurface water, (4) the increase in bottom stress due to the interaction of tidal currents and bottom topography results in the destratification of the bottom water column, and (5) the wind–tide coupled effect. Nevertheless, the exact mechanism dominating the process of a typhoon–tide-induced stronger upper ocean response depends on different typhoon activities, tidal regimes, stratification, and bathymetry and needs further investigations. In this study, we suggest that including tidal effects is essential for the modeling of upper ocean responses to typhoon passages near the shore regions.

Combination Effects of Polyphenols Present in Sugarcane on Proliferation in MCF-7 Human Breast Cancer Cells - Yujiao Yang; Rui Zheng; Pingling Zhang; Jing Wen; Yue Luo; Zhengang Zhao; Lijun You; Chi-Tang Ho (Sugar Tech, 2022)

Synergistic Effect and Mechanism of Apoptosis Induction by Morphine and the HIV-1gp120V3 Loop in Hippocampal Neurons - Xueqin Yan; Zheng Gong; Rui Pan; Huili Wang; Haijie Tang; Hanyang He; Saixian Wen; Yongmei Fu; Jun Dong (Journal of Neuroimmune Pharmacology, 2022)

Pseudonocardia humida sp. nov., an Actinomycete Isolated from Mangrove Soil Showing Distinct Distribution Pattern of Biosynthetic Gene Clusters - Zhen-Yu Zan; Xian-Feng Ge; Rui-Rui Huang; Wen-Zheng Liu (Current Microbiology, 2022)

Microbial ecology of sulfur cycling near the sulfate–methane transition of deep‐sea cold seep sediments - Wen‐Li Li; Xiyang Dong; Rui Lu; Ying‐Li Zhou; Peng‐Fei Zheng; Dong Feng; Yong Wang (Environmental Microbiology, 2021)
Summary Microbial sulfate reduction is largely associated with anaerobic methane oxidation and alkane degradation in sulfate–methane transition zone (SMTZ) of deep‐sea cold seeps. How the sulfur cycling is mediated by microbes near SMTZ has not been fully understood. In this study, we detected a shallow SMTZ in three of eight sediment cores sampled from two cold seep areas in the South China Sea. One hundred ten genomes representing sulfur‐oxidizing bacteria (SOB) and sulfur‐reducing bacteria (SRB) strains were identified from three SMTZ‐bearing cores. In the layers above SMTZ, SOB were mostly constituted by Campylobacterota, Gammaproteobacteria and Alphaproteobacteria that probably depended on nitrogen oxides and/or oxygen for oxidation of sulfide and thiosulfate in near‐surface sediment layers. In the layers below the SMTZ, the deltaproteobacterial SRB genomes and metatranscriptomes revealed CO 2 fixation by Wood–Ljungdahl pathway, sulfate reduction and nitrogen fixation for syntrophic or fermentative lifestyle. A total of 68% of the metagenome assembled genomes were not adjacent to known species in a phylogenomic tree, indicating a high diversity of bacteria involved in sulfur cycling. With the large number of genomes for SOB and SRB, our study uncovers the microbial populations that potentially mediate sulfur metabolism and associated carbon and nitrogen cycles, which sheds light on complex biogeochemical processes in deep‐sea environments.

Genomic molecular signatures determined characterization of Mycolicibacterium gossypii sp. nov., a fast-growing mycobacterial species isolated from cotton field soil - Rui-Rui Huang; Shen-Rong Yang; Cheng Zhen; Xian-Feng Ge; Xin-Kai Chen; Zhi-Qiang Wen; Ya-Nan Li; Wen-Zheng Liu (Antonie van Leeuwenhoek, 2021)

Effects of Diversified Cropping Sequences and Tillage Practices on Soil Organic Carbon, Nitrogen, and Associated Fractions in the North China Plain - Ahmad Latif Virk; Wen-Sheng Liu; Jia-Rui Niu; Cheng-Tang Xu; Qiu-Yue Liu; Zheng-Rong Kan; Xin Zhao; Hai-Lin Zhang (Journal of Soil Science and Plant Nutrition, 2021)

Overexpression of T-type calcium channel Cav3.1 in oral squamous cell carcinoma: association with proliferation and anti-apoptotic activity - Rui-Fang Li; Qi-Wen Man; Jin-Yuan Liu; Yue-Yu Zheng; Xin Gao; Hai-Ming Liu (Journal of Molecular Histology, 2021)

Application of DNA barcoding and metabarcoding for species identification in salmon products - Nan Wang; Ran-Ran Xing; Meng-Yue Zhou; Rui-Xue Sun; Jian-Xun Han; Jiu-Kai Zhang; Wen-Jie Zheng; Ying Chen (Food Additives & Contaminants: Part A, 2021)

Correction to: Exploring the Genetic Association of the ABAT Gene with Alzheimer’s Disease - Quanzhen Zheng; Rui Bi; Min Xu; Deng-Feng Zhang; Li-Wen Tan; Ya-Ping Lu; Yong-Gang Yao (Molecular Neurobiology, 2021)

Exploring the Genetic Association of the ABAT Gene with Alzheimer’s Disease - Quanzhen Zheng; Rui Bi; Min Xu; Deng-Feng Zhang; Li-Wen Tan; Ya-Ping Lu; Yong-Gang Yao (Molecular Neurobiology, 2021)

Protective effect of Lycium barbarum polysaccharide on di-(2-ethylhexyl) phthalate-induced toxicity in rat liver - Rui-jing Liu; Yong-jian He; Huan Liu; Dong-dong Zheng; Shao-wen Huang; Chun-hong Liu (Environmental Science and Pollution Research, 2021)

Rho GTPases in cancer radiotherapy and metastasis - Rui-Jie Zeng; Chun-Wen Zheng; Wan-Xian Chen; Li-Yan Xu; En-Min Li (Cancer and Metastasis Reviews, 2020)

Comparison of volatile profiles and bioactive components of sun-dried Pu-erh tea leaves from ancient tea plants on Bulang Mountain measured by GC-MS and HPLC - Wen-jie Zhang; Cong Liu; Rui-juan Yang; Ting-ting Zheng; Miao-miao Zhao; Li Ma; Liang Yan (Journal of Zhejiang University-SCIENCE B, 2019)

Complete mitochondrial genome of a kind of snakehead fish Channa siamensis and its phylogenetic consideration - Rui Li; Gang Wang; Zheng-Yong Wen; Yuan-Chao Zou; Chuan-Jie Qin; Yu Luo; Jun Wang; Gui-Hong Chen (Genes & Genomics, 2019)

Identification of the complete mitochondrial genome of Garra pingi pingi (Cypriniformes, Cyprinidae) - Yuan-Chao Zou; Mei Chen; Chuan-Jie Qin; Yong-Ming Wang; Rui Li; Ze-Min Qi; Zheng-Yong Wen (Conservation Genetics Resources, 2018)

The complete mitochondrial genome of a threatened loach (Beaufortia kweichowensis) and its phylogeny - Zheng-Yong Wen; Bi-Wen Xie; Chuan-Jie Qin; Jun Wang; Deng-Yue Yuan; Rui Li; Yuan-Chao Zou (Conservation Genetics Resources, 2017)

The complete mitochondrial genome of a threatened loach (Sinibotia reevesae) and its phylogeny - Yuan-Chao Zou; Bi-Wen Xie; Chuan-Jie Qin; Yong-Ming Wang; Deng-Yue Yuan; Rui Li; Zheng-Yong Wen (Genes & Genomics, 2017)

Mitochondrial DNA Haplogroup A Decreases the Risk of Drug Addiction but Conversely Increases the Risk of HIV-1 Infection in Chinese Addicts - A-Mei Zhang; Qiu-Xiang Hu; Feng-Liang Liu; Rui Bi; Bi-Qing Yang; Wen Zhang; Hao Guo; Ian Logan; Yong-Tang Zheng; Yong-Gang Yao (Molecular Neurobiology, 2016)

Alterations and correlations of the gut microbiome, metabolism and immunity in patients with primary biliary cirrhosis - Long‐Xian Lv; Dai‐Qiong Fang; Ding Shi; De‐Ying Chen; Ren Yan; Yi‐Xin Zhu; Yan‐Fei Chen; Li Shao; Fei‐Fei Guo; Wen‐Rui Wu; Ang Li; Hai‐Yan Shi; et al. (Environmental Microbiology, 2016)
Summary We selected 42 early‐stage primary biliary cirrhosis (PBC) patients and 30 healthy controls (HC). Metagenomic sequencing of the 16S rRNA gene was used to characterize the fecal microbiome. UPLC‐MS/MS assaying of small molecules was used to characterize the metabolomes of the serum, urine and feces. Liquid chip assaying of serum cytokines was used to characterize the immune profiles. The gut of PBC patients were depleted of some potentially beneficial bacteria, such as Acidobacteria, Lachnobacterium sp., Bacteroides eggerthii and Ruminococcus bromii , but were enriched in some bacterial taxa containing opportunistic pathogens, such as γ‐Proteobacteria, Enterobacteriaceae, Neisseriaceae, Spirochaetaceae , Veillonella , Streptococcus , Klebsiella , Actinobacillus pleuropneumoniae , Anaeroglobus geminatus , Enterobacter asburiae , Haemophilus parainfluenzae , Megasphaera micronuciformis and Paraprevotella clara . Several altered gut bacterial taxa exhibited potential interactions with PBC through their associations with altered metabolism, immunity and liver function indicators, such as those of Klebsiella with IL‐2A and Neisseriaceae with urinary indoleacrylate. Many gut bacteria, such as some members of Bacteroides, were altered in their associations with the immunity and metabolism of PBC patients, although their relative abundances were unchanged. Consequently, the gut microbiome is altered and may be critical for the onset or development of PBC by interacting with metabolism and immunity.

Oral administration of Anabaena-expressed VP28 for both drug and food against white spot syndrome virus in shrimp - Xiao-Hui Jia; Chun-Li Zhang; Ding-Ji Shi; Min-Min Zhuang; Xiang Wang; Rui Jia; Zheng-Yang Zhang; Jie Huang; Yi-Hua Sun; Wen-Yi Qian; Guo-Hong Peng; Pei-Min He (Journal of Applied Phycology, 2016)

Effects of induced pluripotent stem cells-derived conditioned medium on the proliferation and anti-apoptosis of human adipose-derived stem cells - Rui-Ling Lian; Xiao-Ling Guo; Jian-Su Chen; Yong-Long Guo; Jia-Fu Zheng; Yuan-Wen Chen (Molecular and Cellular Biochemistry, 2016)

Geological and geochronological constraints on the genesis of the giant Tongkuangyu Cu deposit (Palaeoproterozoic), North China Craton - Xuan Liu; Hong-Rui Fan; M. Santosh; Kui-Feng Yang; Zheng-Jie Qiu; Fang-Fang Hu; Bo-Jie Wen (International Geology Review, 2016)

Advanced oxidation protein products induce chondrocyte apoptosis via receptor for advanced glycation end products-mediated, redox-dependent intrinsic apoptosis pathway - Qian Wu; Zhao-Ming Zhong; Si-Yuan Zhu; Cong-Rui Liao; Ying Pan; Ji-Huan Zeng; Shuai Zheng; Ruo-Ting Ding; Qing-Song Lin; Qing Ye; Wen-Bin Ye; Wei Li; et al. (Apoptosis, 2016)

Umezawaea endophytica sp. nov., isolated from tobacco root samples - Xiao Chu; Bing-Bing Liu; Rui Gao; Zheng-Yu Zhang; Yan-Qing Duan; Salam Nimaichand; Wei Chen; Wen-Jun Li (Antonie van Leeuwenhoek, 2015)

Long-Term Effectiveness of Total Hip Replacement with the Collum Femoris Preserving Prosthesis - Rui-jin You; Wen-zhong Zheng; Kun Chen; Hong-sheng Lv; Dian-feng Huang; Yi-zeng Xiao; De-yu Yang; Zhai-quan Su (Cell Biochemistry and Biophysics, 2015)

Statures in Han populations of China - LianBin Zheng; YongLan Li; HuanJiu Xi; KeLi Yu; ShunHua Lu; Rui Shi; YouFeng Wen; JingPing Bao; XingHua Zhang; YuLing Li; Fu Ren; GuoChang Xu (Science China Life Sciences, 2015)

CTLA-4 polymorphisms and systemic lupus erythematosus (SLE): a meta-analysis - Jin-Xia Zhai; Li-Wei Zou; Zhao-Xiang Zhang; Wen-Jing Fan; Han-Yong Wang; Ting Liu; Zheng Ren; Rui-Xue Dai; Dongqing Ye (Molecular Biology Reports, 2013)

Meso-Cenozoic extensional structures in the Northern Tarim Basin, NW China - Yue-Jun Li; Yan Zhao; Long-De Sun; Wen-Jie Song; Duo-Ming Zheng; Ya-Lei Liu; Dao-Xuan Wang; Jian-Feng Hu; Qi-Rui Zhang (International Journal of Earth Sciences, 2013)

Gastrin inhibits a novel, pathological colon cancer signaling pathway involving EGR1, AE2, and P-ERK - Ling-Jun Song; Rui-Jun Liu; Zhi Zeng; Seth L. Alper; Heng-Jing Cui; Yang Lu; Lin Zheng; Zhao-Wen Yan; Guo-Hui Fu (Journal of Molecular Medicine, 2012)

Novel HMW glutenin genes from Aegilops tauschii and their unique structures - Wen-Jie Chen; Zhong-Wei Yuan; Lian-Quan Zhang; Xing Fan; Ze-Hong Yan; Ji-Rui Wang; You-Liang Zheng; Huai-Gang Zhang; Deng-Cai Liu (Genes & Genomics, 2012)

Nicotinic acetylcholine receptor alpha7 subunit is time-dependently expressed in distinct cell types during skin wound healing in mice - Yan-Yan Fan; Tian-Shui Yu; Tao Wang; Wei-Wei Liu; Rui Zhao; Shu-Tao Zhang; Wen-Xiang Ma; Ji-Long Zheng; Da-Wei Guan (Histochemistry and Cell Biology, 2011)

Synthesis, Characterization, DNA-Binding and Antiproliferative Activity of Nd(III) Complexes With N-(Nitrogen Heterocyclic) Norcantharidin Acylamide Acid - Wen-Zhong Zhu; Qiu-Yue Lin; Mei Lu; Rui-Ding Hu; Xiao-Liang Zheng; Jian-Ping Cheng; Yun-Yun Wang (Journal of Fluorescence, 2009)

Transgenic Mice Can Express Mutant Human Coagulation Factor IX with Higher Level of Clotting Activity - Jing-Bin Yan; Shu Wang; Wen-Ying Huang; Yan-Ping Xiao; Zhao-Rui Ren; Shu-Zheng Huang; Yi-Tao Zeng (Biochemical Genetics, 2006)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)